2021
DOI: 10.3389/fimmu.2021.663748
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Immune Profiling for Survival of Multiple Myeloma Patients

Abstract: Despite new efficacy drugs and cell therapy have been used for multiple myeloma (MM) patients, some patients will relapse over time. We wonder the immune system play a vital role as well as MM cell during the development of disease. It is clear that the characteristic of myeloma cell is associated with the survival of MM patients. However, the link between the immune profiling and the prognosis of the disease is still not entirely clear. As more study focus on the role of immunity on multiple myeloma pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 102 publications
(148 reference statements)
0
11
0
Order By: Relevance
“…The immune profiling may play a crucial role in the outcome of MM [19], but probably only a complete immune evaluation will successfully predict survival in MM patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…The immune profiling may play a crucial role in the outcome of MM [19], but probably only a complete immune evaluation will successfully predict survival in MM patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences show that NK cells paly a central role in anti-tumor e cacy due to their ability to spontaneously kill tumor cells 27,28 . To date, MM has still been an enduring conundrum.Since immune dysfunction have been reported as an important part for disease progression and even in uence survival of MM patients 29,30 . Taking more study on immune cell and develop immune therapy will be a new choice for MM patients.As previous reported that the count of NK cell were increased in MM patients,but the function show exhausted 31 .Considering the advantage of NK cell count in MM patients and kill malignant cells without prior sensitization,it is easy for us to think to make a full use of NK cell to antimyeloma cell.In fact,there have been reported some way to use NK cell in MM patients investigation,like active NK cell function choice Daratumumab 32 and SLAMF7 antibody 33 , the other way is the using targeting NK cell inhibitory receptors including TIGIT, PD-1 and TIM-3 10 .However,new ways still needed since the complex regulation of NK cell function and MM immune micro-environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the progression of MM was not noly related to MRD,but also closely related to the exhaustion of functional immune cells, and the suppression of regulatory immune cells. [15]. Previous studies had shown that applying ow cytometry can also analyze T cells in multiple myeloma patients, and that T cell subsets such as Treg have an important role in assessing MM patient prognosis.…”
Section: Discussionmentioning
confidence: 99%